Preparation method of NZVI-PVDF hybrid films with cation-exchange function for reductive transformation of Cr(VI) - Wang, Xiangyu; Cong, Shan (Journal of Environmental Engineering and Landscape Management, 2018)
Poly (vinylidene fluoride) (PVDF) microporous film was successfully synthesized and functionalized by poly acrylic acid (PAA) for immobilization of nanoscale zero-valent iron (NZVI). PAA was innovatively introduced onto PVDF film via in situ polymerization of acrylic acid (AA) and followed by ion exchange procedure. The as-prepared PAA/PVDF-NZVI hybrids (PPN) were characterized in terms of morphology (SEM) and surface functional groups (FTIR). FTIR spectra confirms the functionalization of PVDF film by coating of PAA within its micropores. And SEM images suggested that NZVI were well immobilized onto the surface of the support. Over the reaction course, the resultant PPN hybrids demonstrated high reactivity, excellent stability and reusability for Cr(VI) removal. Results showed that lower pH and initial concentration facilitated the removal of Cr(VI) by PPN. Compared with bare NZVI, PAA/PVDF film-immobilized NZVI resulted in a lower activation energy for Cr(VI) removal, indicating that Cr(VI) reduction process with PPN is a surfacecontrolled chemical reaction. Moreover, a two-parameter pseudo-first-order model was provided and well-described the reaction kinetics of Cr(VI) over PPN under various conditions.